2022
DOI: 10.3390/polym14173566
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Based Composites for Light Automotive Parts: Statistical Analysis of Mechanical Properties; Effect of Matrix and Alkali Treatment in Sisal Fibers

Abstract: Composites based on virgin and recycled polypropylene (PP and rPP) reinforced with 15 wt% sisal fibers, with and without alkali treatment, were prepared by compression molding in a mat composed of a three-layer sandwich structure. The sisal was characterized by Fourier-transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD). The composites were characterized according to physical and mechanical properties. Additionally, a factorial experimental design was used to statistically evaluate the mechanica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…The impact strength results demonstrate that the impact resistance of the 0-100-0 sample in this study, measured at 24.32 ± 5.61 KJ/m 2 , as consistent with the literature findings [ 15 , 21 , 96 ]. However, the impact strength decreased as the amount of hemp fiber added to the formulations increased compared to pure PP.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The impact strength results demonstrate that the impact resistance of the 0-100-0 sample in this study, measured at 24.32 ± 5.61 KJ/m 2 , as consistent with the literature findings [ 15 , 21 , 96 ]. However, the impact strength decreased as the amount of hemp fiber added to the formulations increased compared to pure PP.…”
Section: Resultssupporting
confidence: 92%
“…The incorporation of natural fibers in biocomposites has demonstrated significant benefits, providing improved properties and reducing environmental impact when compared to conventional composites. This growing trend in the use of natural fibers is in line with the global push towards a more sustainable economy and the industrial adoption of green materials [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…A few bands in the 1500-1200 cm -1 region to both CH 2 deformations and C-O-H bending vibrations, and intense bands in the 1200-900 cm -1 region are attributed to the stretching modes of C-O and C-C vibrations. The bands from 800 to 700 cm -1 represent the contributions from two crystalline forms of cotton cellulose, in which the type of cellulose is associated with the plant's origin and can directly influence the mechanical properties of cotton [59][60][61][62] .…”
Section: Ftir Resultsmentioning
confidence: 99%
“…The authors mentioned the need to investigate other parameters to achieve the specified requirements. Silva et al [274] evaluated the performance of polyester matrix composites reinforced with different fibers in impact and bending tests. For comparison, they used raffia, jute, mallow, piassava, and sisal fibers as reinforcements in similar compositions.…”
Section: Piassavamentioning
confidence: 99%
“…In addition, its use contributes to the preservation of the environment, as piassava is a native plant and its sustainable extraction promotes the Based on the results obtained, the authors observed that piassava fibers have high resistance compared to other fibers such as mallow, raffia, and jute, although their performance was slightly lower than the composite with sisal fibers. Among all natural fibers, sisal is one of the most resistant, if not the most resistant natural fiber among the species [273,274].…”
Section: Piassavamentioning
confidence: 99%